Mapping the effect of plant‐based extracts on immune and tumor cells from a bioactive compound standpoint - Chujun Huang; Tianxiong Xu; Yanping Li; Jiaoyan Ren (Food Frontiers, 2023)
Abstract Instead of traditional regimen of “one molecule, one target, one disease,” natural plant extracts, as a multi‐component system, show great potential in alleviate disease with complex etiology and pathophysiological factors, such as cancer. In this study, we evaluated the chemical characteristic as well as bioactive activities profiles of 15 species of plant‐based extracts, which corresponding to polysaccharide, protein, polyphenol content, and effects on MC38, LLC, RAW264.7 cell viability, respectively. Person correlation analysis and multi‐criteria decision analysis method was proposed to evaluate dose‐effect relationship and the comprehensive activities of each extract. A significant positive correlation was found between polyphenol value and immune cell activity, which means that it was considered to perform well on antitumor and immunomodulatory effects when compared to the studied substances. The subsequent measurement by a MC38‐N4/OT‐I coculture model verified the results, showing an excellent effect of Grifola frondosa on enhancing the antigen‐specific killing of tumor cells. Here we give a general view of the chemical composition and the bioactive activities of 15 plant‐based extracts and provide a feasible strategy to estimate the complex effect of phytochemicals. That would help us to better understand the effect of phytochemical combination and lay a good foundation for further in vivo studies.